Prenatal and Obstetric Risk Factors for Development of Disabilities in Childhood - Ksenija Romstein; Dubravko Habek; Tena Velki; Maja Košuta Petrović (Acta Clinica Croatica, 2024)
The main objective was to analyze prenatal and obstetric risk factors in relation to the development of disabilities. For that purpose, data on medication, i.e., use of benzodiazepines during pregnancy, gestational weeks, mode of delivery (vaginal or cesarean section), duration of delivery, and fetal presentation were retrieved from medical records and semi-structured interviews with mothers/legal guardians. Trained professionals clinically assessed the children’s developmental status (N=107). Fisher exact test with post hoc analysis of standardized residuals showed that a statistically significant number of children with multiple disabilities were born by cesarean section (z=3.7, p<0.001), prematurely (z=4.8, p<0.001), and by mothers using benzodiazepines (z=2.6, p<0.01). Children with autism spectrum disorders were more often delivered post-term (z=2.0, p<0.05) by induced delivery (z=2.9, p<0.01). Children with developmental coordination disorder were more often born post-term (z=2.2, p<0.05). As for the duration of delivery and fetal presentation, there was no statistically significant correlation with developmental disabilities. There is a cumulative risk of developmental disabilities rather than just a single risk factor. More interdisciplinary and longitudinal research on developmental disabilities, including children’s educational outcomes should be conducted.